Conditional deletion of Hdac3 in osteoprogenitor cells attenuates diet-induced systemic metabolic dysfunction. (15th July 2015) - McGee-Lawrence, Meghan E.; White, Thomas A.; LeBrasseur, Nathan K.; Westendorf, Jennifer J.
Highlights: Osteoblastic expression of Hdac3 is required for normal bone maintenance. Osteoprogenitor-specific Hdac3 CKO mice were leaner with low fasting glucose levels. Hdac3 CKO mice maintained insulin sensitivity on a prolonged high fat diet. Hdac3 CKO mice prevented hepatic steatosis on a prolonged high fat diet. Hdac3 is involved in the paradigm of skeletal regulation of energy metabolism. Abstract: Obesity is a major health epidemic in the United States and a leading cause of preventable diseases including type 2 diabetes. A growing body of evidence indicates that the skeleton influences whole body metabolism and suggests a new avenue for developing novel therapeutic agents, but the underlying mechanisms are not well understood. Here, it is demonstrated that conditional deletion of an epigenetic regulator, Hdac3, in osteoblast progenitor cells abrogates high fat diet-induced insulin resistance and hepatic steatosis. These Hdac3-deficient mice have reduced bone formation and lower circulating levels of total and undercarboxylated osteocalcin, coupled with decreased bone resorption activity. They also maintain lower body fat and fasting glucose levels on normal and high fat chow diets. The mechanisms by which Hdac3 controls systemic energy homeostasis from within osteoblasts have not yet been fully realized, but the current study suggests that it does not involve elevated levels of circulating osteocalcin. Thus, Hdac3 is a new player in the emerging paradigm that the skeleton influences systemic energy metabolism.